Empreendimentos solidários e suas estratégias para o desenvolvimento local: estudo de caso da comunidade de Ipueira, Severiano Melo-RN - Dantas, Márcia Egina Câmara (2013)
Solidary economic enterprises are characterized as those guided self-management, participatory, democratic, based on self-sustainability and human development. In this sense research the objetive is to analyze the process of project management supportive rural community in the municipality of Ipoeira Severiano Melo - RN in view of the solidarity economy and its impact on economic development process of the members of the AAFI. This research is a case study. As for the means bibliographical research, documentary and field where questionnaires were administered to the members active and not active in the project in order to obtain participation and how is the development of the activities of the partners. With the data obtained it was possible to analyze the variables that affect the degree of participation of the partners in the association and identify the main difficulties it faces from the point of view of its members. It was found, therefore, in regard to the difficulties pointed out by the main partners were: lack of unity, the process of decision making and lack of organization. As for income generation was observed that for most of the subjects bind the association improved its income. Regarding the variables that affect the degree of participation in the project has been possible to identify people females, aged 20-39 years, who have a considerable amount of family members have a greater tendency to participate in the venture